Flood risk management - Miren Sarasíbar Iriarte (Revista d'Estudis Autonòmics i Federals)
This article discusses flood risk management in Spanish law in light of the flood disaster that occurred in Valencia a few months ago. The starting point is climate change as the main cause of flooding, combined with human intervention, in altering the natural course of water. Emphasis is placed on the vulnerability of people and certain areas, as well as on the management of the risk of flooding as an environmental problem and a disaster in terms of civil protection. The article concludes with a brief reference to the specific management of the flood disaster that occurred a few months ago, which had serious consequences at all levels, especially the loss of numerous lives.